A new species of Cogia from Oaxaca, Mexico (Lepidoptera: Hesperiidae: Eudaminae) - Warren, Andrew D.; Dolibaina, Diego R.; Hernández-Mejía, Claudia (Zootaxa, 2015)
A new species of Cogia A. Butler, 1870, is described from two localities ranging from 1470 to 2000 m elevation in the Sierra Madre del Sur of Oaxaca, Mexico; it occurs in cloud forest habitats and appears to be endemic to Mexico. Cogia buena, n. sp., is closely related to C. mala Evans, 1953 and C. aventinus (Godman & Salvin, 1894); these three species are the only known Cogia taxa whose males lack a hair tuft on the dorsal hindwing, and all have similar genitalia.